Virtuous Organizational Practices: A New Construct and a New Inventory - Aubouin-Bonnaventure, Julia; Fouquereau, Evelyne; Coillot, Hélène; Lahiani, Fadi Joseph; Chevalier, Séverine (Frontiers in Psychology, 2021)
Research on the identification of organizational practices that promote individual and organizational performance is now very extensive. However, several studies have revealed the dark side of these practices on employees’ psychological health. Consequently, researchers have called on the scientific community to focus on the well-being of workers and to identify the organizational practices that promote it. Thus, the aim of the present research was to fill this gap by introducing a new conceptualization of organizational practices supporting the psychological health of employees and proposing a new improved measure to assess them. Drawing on the American Psychological Association’s model of Psychologically healthy workplace, we first conceptualized the innovative multidimensional construct of virtuous organizational practices. We then conducted four studies (N = 1,407) to develop and validate the Virtuous Organizational Practices inventory. Results of exploratory statistical analyses provide strong evidence of the second-order factor structure of the inventory in different French samples and of the convergent, predictive and incremental validity of this tool. Implications for researchers, organizations and practitioners and avenues for future research are discussed.